Three-dimensional kinematic differences between turning skill level and radius during alpine skiing - Joo-Nyeon Kim (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to investigate the three dimensional joint angles of the ankle, knee and hip during basic long turn, carving long turn, basic short turn and carving short turn. Methods Fourteen alpine ski instructors from Korea Ski Instructor Association participated in this study. Each skier asked to perform 4-types of turning technique, classified by radius and level. 8 inertial measurement units were used to measure three-dimensional joint angles of the ankle, knee and hip joint. Results Significant differences were found the lower extremity joint angles on the mediolateral and vertical axis during long-turn and carving-turn (p<.05). significant differences were found the lower extremity joint angles on the anteroposterior axis in the steering phases 1, 2 and complete phase (p<.05). Conclusions In the Alpine skiing, the short turn requires a complex movement of the lower limb joint compared to the long turn. When performing a long turn, the movement of the ankle joint on the vertical axis are required compared to the short turn. And the carving and short turn need to the movements of the lower limb joint on the mediolateral axis.